Flor de muertos - Vinik, Danny; Calexico (Musical group); Sonication Films; Brink Films; Soundview Media Partners ([Tucson, Ariz.] : Sonication Films : Brink Films, 2011)
A celebratory journey into the rich borderlands culture between Tucson, Arizona and the towns of Nogales, Arizona and Mexico. Director Danny Vinik evokes the power and beauty of the Sonoran Desert and its people in this poetic exploration of life and death along the US/Mexico border. Features a stunning performance by acclaimed Americana band Calexico at Tucson's historic Rialto Theatre.
Originally released as a motion picture in
Featuring Calexico live in concert at the Rialto Theatre in Tucson, Arizona.
Cinematographer, Lisa Rinzler ; editor, Jim Rundel ; music, Calexico.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: All Souls' Day -- Mexican-American Border Region; Emigration and immigration -- Social aspects; Mexican-American Border Region -- Social life and customs; Documentary films; Nonfiction films; Internet videos; Streaming video